Probiotics (Bacillus clausii and Lactobacillus fermentum NMCC-14) Ameliorate Stress Behavior in Mice by Increasing Monoamine Levels and mRNA Expression of Dopamine Receptors (D1 and D2) and Synaptophysin - Rehman, Mujeeb Ur; Ghazanfar, Shakira; Ul Haq, Rizwan; Ullah, Shakir; Khan, Salman; Wu, Jianbo; Ahmad, Waqar; Tipu, Muhammad Khalid (Frontiers in Pharmacology, 2022)
Stress is a physiological consequence of the body to adversity. The gut–brain axis and probiotics are gaining interest to provide better treatment for stress and other neurological disorders. Probiotic (Lactobacillus fermentum NMCC-14 and Bacillus clausii, 1010 colony-forming unit/day/animal, per oral) effects were investigated in acute (up to day 7) and subacute (days 8–14) restraint-stressed and normal mice through behavioral paradigms (elevated plus maze: EPM, light dark box/dark light box: LDB, and open field test: OFT). Time spent in the open arms of the EPM, time spent in the light compartment of the LDB, and movable time and time spent in the center of the OFT were significantly (p ≤ 0.05, n = 5) increased in probiotic-treated restraint-stressed mice. Enzyme-linked immunoassay determined blood cortisol and adrenocorticotropic hormone (ACTH) levels, which were reduced significantly (p < 0.05, n = 5) in probiotic-treated restraint-stressed mice. Hematoxylin and eosin-stained hippocampal slides also showed less or no neurodegeneration in the probiotic-treated animals. High-performance liquid chromatography and quantitative polymerase chain reaction were performed to determine the monoamine levels and mRNA expression of dopamine receptor subtypes (D1 and D2) and synaptophysin in the mice hippocampus (HC) and prefrontal cortex (PFC). The dopamine, serotonin, and norepinephrine levels were also significantly (p < 0.05, n = 5) increased in the HC and PFC of probiotic-treated animal brains. Fold expression of mRNA of D1 and D2 (except HC, LF-S, day 14) receptors and synaptophysin was also significantly (p < 0.05, n = 5) increased in the same brain parts of probiotic-treated restraint-stressed mice. Comparing mice in the Lactobacillus fermentum NMCC-14 and Bacillus clausii groups to mice in the normal group, only a significant (p < 0.05, n = 5) decrease was observed in the serum ACTH and cortisol levels on day 14 in Bacillus clausii-treated mice, where all other parameters also showed improvement. In comparison, Bacillus clausii showed greater stress suppressant activity than Lactobacillus fermentum NMCC-14. However, both probiotic bacteria can be a better and safer therapeutic alternative for ailments than currently available drugs.